Zinc and multivitamin supplementation have contrasting effects on infant iron status: a randomized, double-blind, placebo-controlled clinical trial - Carter, R C; Kupka, R; Manji, K; McDonald, C M; Aboud, S; Erhardt, J G; Gosselin, K; Kisenge, R; Liu, E; Fawzi, W; Duggan, C P (European journal of clinical nutrition, 2018)
Background/Objectives: Zinc (Zn) supplementation adversely affects iron status in animal and adult human studies, but few trials have included young infants. The objective of this study was to determine the effects of Zn and multivitamin (MV) supplementation on infant hematologic and iron status. Subjects/Methods: In a double-blind RCT, Tanzanian infants were randomized to daily, oral Zn, MV, Zn and MV or placebo treatment arms at the age of 6 weeks of life. Hemoglobin concentration (Hb) and red blood cell indices were measured at baseline and at 6, 12 and 18 months of age. Plasma samples from 589 infants were examined for iron deficiency (ID) at 6 months. Results: In logistic regression models, Zn treatment was associated with greater odds of ID (odds ratio (OR) 1.8 (95% confidence interval (CI) 1.0–3.3)) and MV treatment was associated with lower odds (OR 0.49 (95% CI 0.3–0.9)). In Cox models, MV was associated with a 28% reduction in risk of severe anemia (hazard ratio (HR)=0.72 (95% CI 0.56–0.94)) and a 26% reduction in the risk of severe microcytic anemia (HR=0.74 (0.56–0.96)) through 18 months. No effects of Zn on risk of anemia were seen. Infants treated with MV alone had higher mean Hb (9.9 g/dl (95% CI 9.7–10.1)) than those given placebo (9.6 g/dl (9.4–9.8)) or Zn alone (9.6 g/dl (9.4–9.7)). Conclusions: MV treatment improved iron status in infancy, whereas Zn worsened iron status but without an associated increase in risk for anemia. Infants in long-term Zn supplementation programs at risk for ID may benefit from screening and/or the addition of a MV supplement.